Ultrastructural changes of optic nerve in experimental model of eye contusion in rabbits (Ukrainian Journal of Ophthalmology, 2026)
Introduction: Direct and indirect injuries can lead to decrease of visual acuity in the eye or head traumas.Purpose: To study ultrastructure of the optic nerve of rabbits after experimental mild contusion.Material and methods: We examined 20 eyes. Electron microscopy of the op¬tic nerve was made after experimental mild eye contusion in 1 week, 1 month, 2 months.Results: Postcontusional disorders were found in neurofilaments, neurotubules, axonal mitochondria.Conclusion: Early and first ultrastructural changes of the optic nerve were found in experimental mild eye contusion in 1 week, 1 month, 2 months. The main disor¬ders were found in neurofilaments, neurotubules, axonal mitochondria.
Keywords: optic nerve; contusion of the eyeball; ultrastructural changes